(untitled) (Nexus International Journal of Science and Education, 2024)
This study explored the experiences of teachers’ burnout in the classroom. Specifically, it aimed to answer their perceptions about it simultaneously as the coping mechanisms for the emerging challenges. To achieve the objectives of the study, I made use of phenomenology. The 10 participants of this study were female teachers of Panibasan Elementary School, Maco North District, Davao de Oro Division. I used a semi-structured online interview using the coding technique to analyze the data. The study disclosed different themes, such as in the first Objective, experiences of teachers' burnout in the workplace. The results were excessive workload, student challenges, underpaid, and lack of incentives. The second objective is to provide Coping strategies for teachers to the challenges they perceive as effective in preventing workplace burnout. in collecting results, themes are self-care and time management. In summary, these emergent themes provide insights that emphasize the significance of holistic approaches to teacher well-being. Educational institutions and legislators may support a more resilient and contented teaching workforce by cultivating a culture that prioritizes work-life balance, supports self-care, and offers tools for efficient time management. It was essential to identify and address these coping mechanisms to foster an atmosphere in which educators can flourish on the job while preserving their general well-being. In order to avoid becoming overburdened, educators understand the importance of setting limits, prioritizing work, and effectively managing their workload. Teachers may benefit from professional development options that emphasize time management techniques. Providing tools and resources to educators that facilitate task streamlining, good planning, and goal-setting leads to a more sustainable workload.